2016
DOI: 10.1186/s13613-016-0204-y
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-3 definitions predict ICU mortality in a low–middle-income country

Abstract: BackgroundSepsis-3 definitions were published recently and validated only in high-income countries. The aim of this study was to assess the new criteria’s accuracy in stratifying mortality as compared to its predecessor (Sepsis-2) in a Brazilian public intensive care unit (ICU) and to investigate whether the addition of lactate values would improve stratification.MethodsRetrospective cohort study conducted between 2010 and 2015 in a public university’s 19-bed ICU. Data from patients admitted to the ICU with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
2
34
0
3
Order By: Relevance
“…Our findings could support the use of SOFA scores even in a resource‐limited ward setting, although it is unclear how this might best be integrated into already established track and trigger systems . Donnelly et al were able to show in a population‐based study that high admission SOFA was the best tool predict poor outcome in the hospital and within one year after discharge, with similar AUROC (0.765) and HR 2.43 (95%CI 1.84–3.21) to ours .…”
Section: Discussionsupporting
confidence: 81%
“…Our findings could support the use of SOFA scores even in a resource‐limited ward setting, although it is unclear how this might best be integrated into already established track and trigger systems . Donnelly et al were able to show in a population‐based study that high admission SOFA was the best tool predict poor outcome in the hospital and within one year after discharge, with similar AUROC (0.765) and HR 2.43 (95%CI 1.84–3.21) to ours .…”
Section: Discussionsupporting
confidence: 81%
“…A number of prior studies have evaluated methods for identifying high risk infection patients in various settings. 4, 6, 2631 Iwashyna, et al examined the validity of claims-based algorithms for identifying sepsis relative to events defined clinically based on prior international consensus criteria, finding high specificity and positive predictive values with modest sensitivity. 26 Gaieski, et al examined several methods for identifying sepsis in administrative data and found striking differences the total burden of sepsis and temporal trends in incidence depending on the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies appear to validate the criteria in both low-middle and developing countries [109][110][111], although this is relatively limited in scope. There are also two large prospective evaluations of the predictive model in the literature from the United States and Australia [112,113].…”
Section: How Can We Screen For Sepsis In Varied Settings?mentioning
confidence: 99%